Preliminary Evaluation of a NitrAdine-Based Brushing Solution for Patients Suffering from Gingivitis: A Prospective Clinical Case–Control Study - Perelli, Michele; Abundo, Roberto; Semenza, Mario; Centracchio, Mauro; Chiara, Stefano Di; Monaco, Andrea; Arduino, Paolo Giacomo (European Journal of Dentistry, 2021)
Objectives This article aimed to evaluate the clinical efficacy of a nonantibiotic biofilm-removal formulation based on NitrAdine (PerioTabs), combined with a regular home oral hygiene regimen, in Caucasian patients with gingivitis.Materials and Methods A sample of 60 patients were included in this clinical prospective study. All selected subjects underwent regular prophylaxis and professional oral hygiene at baseline; 30 days later, they were recalled for the measurements of the reference parameters about bleeding on probing (full-mouth bleeding upon probing score [FMBS]) and plaque index (full-mouth plaque score [FMPS]); no other clinical procedure was performed. Consequently, half of the patients (n = 30) were instructed to use PerioTabs for 10 days. The remaining patients (n = 30) were used as the negative control, only instructed to continue with their usual oral hygiene regimen. Fifteen days after, the clinical parameters of FMBS and FMPS were re-evaluated in both groups.Results Changes in the scores of clinical indices FMBS and FMPS were calculated and compared. A significant difference between pre- and post-values, for both FMBS and FMPS, was noticed in the test group; in particular, the bleeding index value demonstrated the more significant changes: 22 participants showed a clinically meaningful improvement, and 5 had a small improvement. Only three patients had no evidence of change. In addition, 50% of patients had a reduction in plaque levels. No side effects were reported.Conclusions The adjunctive use of 10-day PerioTabs treatment in the daily oral hygiene routine seemed to be efficient in reducing gingival bleeding and plaque accumulation, with absence of adverse effects. These results should be confirmed in studies with a larger number of participants following a controlled-blinded design.
Keywords: PerioTabs; open-label; gingivitis; outcome